Meningkatkan Keterbukaan Diri Dalam Komunukasi Antar Teman Sebaya Melalui Bimbingan Kelompok Teknik Johari Window - Hanifa, Sania Nur; Sugiyo, Sugiyo; Setyowani, Ninik (Universitas Negeri Semarang, 2012)
This research was conducted based on the phenomenon that is in high school Walisongo Pecangaan Jepara indicating students who have low self-disclosure in the communication between peers. The purpose of this study to determine the efficacy in improving transparency in the communication between peers through group guidance Johari window techniques. This techniques type of research used in this study is experimental research. Sample were 10 students who have low self-disclosure in personal communication between peers. Methods of data collection using psychological scales. Wilcoxon test results obtained Thitung 55.0 > 8.0 TTable or imply Ha accepted and Ho rejected. These results indicate the level of openness in communication among peers increased after receiving group guidance Johari window technique. These results demonstrate openness in communication among peers before getting group guidance Johari window technique 57.5% with medium category and guidance johari window technique after gaining guidance johari window technique 76.5% with high category. The difference in levels of self-disclosure of students before and after the technical guidance of Johari window by 19%. In addition, students progressing better behavior seen from the increasing some indicators such as, be objective, provisional, understand yourself, understand others, adopted a trusting and open attitude.